Strangers at the gates movements and states in contentious politics - Tarrow, Sidney G. (Cambridge University Press, 2012)
This book contains the products of work carried out over four decades of research in Italy, France and the United States, and in the intellectual territory between social movements, comparative politics, and historical sociology. Sidney Tarrow places social movements in the broader arena of contentious politics, in relation to states, political parties and other actors.